Are Groote Schuur Hospital anaesthesiologist burnt out? A cross-sectional study of prevalence and risk - Groenewald, Michael Burger (Department of Anaesthesia and Perioperative Medicine, 2021)
Background: Burnout and physician wellness are becoming increasingly topical. While some surveys have been performed with South African anaesthesiologists, these have been conducted in limited samples. While Burnout is often measured, there is a paucity of research on contributory risk and protective factors. Method: A contextual, prospective, cross-sectional study was conducted. The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and the Areas of Work-Life Survey (AWS) were used to assess Burnout and contributory organizational risk factors amongst state-employed anaesthesiologists working at Groote Schuur Hospital. Results: Out of a possible 127 members of staff (Medical officers, Registrars and Consultants), 81 responded with 75 completing the full survey (59% response rate). Only 4% of respondents were classified as “burnt out”, defined as scoring 8 high in all three domains of Burnout: High Emotional Exhaustion and Depersonalization and Low Personal Accomplishment. However, 67% of respondents scored high for at least one of the components of Burnout, indicating the majority of the respondents are at risk for developing clinically significant Burnout. The Areas of Work-Life survey showed that respondents found their workload inappropriate. However, responses for the categories of Control, Reward, Community, Fairness and Values were all in the acceptable range. Conclusion: While the overall rate of Burnout was low, the majority of respondents were at risk of developing Burnout. High perceived workload appeared to be a particular contributory factor. Protection against Burnout in this group may be provided by a combination of few organisational risk factors together with feelings of personal accomplishment.